PENGARUH PROMOSI, KEMUDAHAN PENGGUNAAN, DAN KEPERCAYAAN KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA ONLINE MARKETPLACE (Studi pada Konsumen Tokopedia di Universitas Diponegoro) - Iqbal, Muhammad; Yoestini, Yoestini (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to determine whether there is an effect of promotion, ease of use, and trust on purchasing decisions among students who use Tokopedia in the city of Semarang. This study uses primary data obtained from direct interviews and distributing questionnaires to 100 respondents. The sampling technique in this study used a non-probability method with a purposive sampling approach. Then the data that has been collected is processed using IBM SPSS software. The results of this study indicate that promotion has a significant positive influence on purchasing decisions, ease of use has a significant positive influence on purchasing decisions, and trust has a significant positive influence on purchasing decisions for Tokopedia consumers in the city of Semarang.